Penerapan manajemen risiko pada pembiayaan perbankan syariah untuk meminimalkan kerugian - Rifqi, Muhammad (Maliki Interdisciplinary Journal, 2024)
This journal discusses the application of risk management in sharia banking financing. Sharia banking has certain risks, especially financing risk which is caused by the possibility that customers cannot repay the financing. This can cause losses for the bank. Therefore, implementing effective risk management is important for Islamic banks. Risk management functions to recognize, measure, track and manage financing risks optimally. In this way, Islamic banks can minimize potential losses due to customer failure to pay and increase their financial stability. This journal also discusses the types of risks that sharia banking may face, such as credit, market, liquidity and operational risks. Proper risk management with risk management methods can provide benefits for banks to minimize the risk of loss.